Comparative chloroplast genome analysis of Sambucus L. (Viburnaceae): inference for phylogenetic relationships among the closely related Sambucus adnata Wall. ex DC Sambucus javanica Blume - Waswa, Emmanuel Nyongesa; Mkala, Elijah Mbandi; Odago, Wyclif Ochieng; Amenu, Sara Getachew; Mutinda, Elizabeth Syowai; Muthui, Samuel Wamburu; Ding, Shi-Xiong; Hu, Guang-Wan; Wang, Qing-Feng (Frontiers in Plant Science, 2023)
Sambucus L. is found in the family Viburnaceae (syn. Adoxaceae) and encompasses approximately 29 accepted species. The complex morphology of these species has caused continued confusions concerning their nomenclature, classification, and identification. Despite previous attempts to resolve taxonomic complexities in the Sambucus genus, there are still unclear phylogenetic relationships among several species. In this study, the newly obtained plastome of Sambucus williamsii Hance. as well as the populations of Sambucus canadensis L, Sambucus javanica Blume, and Sambucus adnata Wall. ex DC were sequenced, and their sizes, structural similarity, gene order, gene number, and Guanine-Cytosine (GC) content analysed. The phylogenetic analyses were conducted using the whole chloroplast genomes and Protein-Coding Genes (PCGs). The findings revealed that the chloroplast genomes of Sambucus species exhibited typical quadripartite double-stranded DNA molecules. Their lengths ranged from 158,012 base pairs (bp) (S. javanica) to 158,716 bp (S. canadensis L). Each genome comprised a pair of Inverted Repeats (IRs) which separated the Large Single-Copy (LSC) and the Small Single-Copy (SSC) regions. In addition, the plastomes contained 132 genes, encompassing 87 protein-coding, 37 tRNA, and four rRNA genes. In the Simple Sequence Repeat (SSR) analysis, A/T mononucleotides had the highest proportion, with the most repetitive sequences observed in S. williamsii. The comparative genome analyses showed high similarities in structure, order, and gene contents. The hypervariable regions in the studied chloroplast genomes were trnT-GGU, trnF-GAA, psaJ, trnL-UAG, ndhF, and ndhE, which may be used as candidate barcodes for species discrimination in Sambucus genus. Phylogenetic analyses supported the monophyly of Sambucus and revealed the separation of S. javanica and S. adnata populations. Sambucus chinensis Lindl. was nested within S. javanica in the same clade, collaborating their conspecific treatment. These outcomes indicate that the chloroplast genome of Sambucus plants are valuable genetic resources for resolving taxonomic discrepancies at the lower taxonomic levels and can be applied in molecular evolutionary studies.